2021
DOI: 10.52417/ojmr.v2i2.240
|View full text |Cite
|
Sign up to set email alerts
|

Health-Related Quality of Life of Health Professionals in a Tertiary Health Institution of Southwestern Nigeria: A Cross-Sectional Survey

Abstract: Introduction: Health professionals (HP) are frequently exposed to a high number of hazards at the workplace. Consequently, low ratings for their well-being and satisfaction with health care may adversely affect the quality of health services they provide. This study aimed to assess health-related quality of life (HRQOL) and determine the effects of socio-demographic variables on HRQOL across HP in a tertiary health institution in Nigeria, a low-middle-income economy. Method: This was a cross-sectional survey o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…This finding aligns with a previous study by Fadare et al, (2014) who also reported a female preponderance of 64%. The most reported professional qualification is the MBBS degree of medical doctors, closely followed was the Bachelor of Science degree which is the minimum entry-level qualification for all other HPs, hence, their high proportion in this study is consistent with a previous study by Odetunde et al, (2021).…”
Section: Resultssupporting
confidence: 88%
“…This finding aligns with a previous study by Fadare et al, (2014) who also reported a female preponderance of 64%. The most reported professional qualification is the MBBS degree of medical doctors, closely followed was the Bachelor of Science degree which is the minimum entry-level qualification for all other HPs, hence, their high proportion in this study is consistent with a previous study by Odetunde et al, (2021).…”
Section: Resultssupporting
confidence: 88%